Analysis of Student Needs in Developing Pancasila Learning Media Based on AI Avatar Generator: Developing Character Education in the Digital Era - Catur Puji Hastuti; Umi Chotimah; Evy Ratna Kartika Waty (STAI Hubbulwathan Duri, 2025)
This study investigates the use of AI Avatar Generator-based learning media to enhance students’ understanding of Pancasila education in junior high schools, focusing on student perceptions in Lahat Regency. Traditional instructional methods are often perceived as less engaging, underscoring the need for innovative approaches to improve educational outcomes. A quantitative descriptive design was employed. Data were collected via purposive sampling from students at several junior high schools in Lahat Regency. An online questionnaire with closed-ended questions was used to assess students’ views on the importance of Pancasila education, their level of understanding, and their preferences for technology-based learning. Descriptive statistical analysis revealed that 80% of respondents acknowledged the high importance of Pancasila education, yet only 65% reported a full understanding of the material. Additionally, 89% of students showed strong enthusiasm for the integration of AI Avatar Generators in the learning process. Findings indicated that conventional teaching methods remain dominant and are viewed as insufficiently engaging. The results suggest that AI Avatar Generator-based media may bridge the gap between traditional teaching and students’ expectations for interactive learning. By offering personalized and engaging content, this technology has the potential to improve comprehension and foster greater student interest in Pancasila education.